Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/257369
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit Hyperactive Disorder among Primary School Children in Menoufia Governorate, Egypt

Abstract: Background. Attention-deficit hyperactivity disorder (ADHD) is the most commonly diagnosed behavioral problem in children. Global variations in diagnostic criteria and rating scales of ADHD either by DSM-IV or ICD 10 may contribute to variations in its prevalence. Objectives. The study was conducted to estimate the prevalence of ADHD and to determine its risk factors. Methodology. A cross-section comparative study was conducted in a randomly selected four primary schools in Menoufia governorate, Egypt. All chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 19 publications
(27 reference statements)
6
24
1
Order By: Relevance
“…Regarding gender, this study found significantly higher prevalence of ADHD among boys (14.5) than girls (3.6). This is consistent with results reported by studies conducted in Egypt 11,15,16,18 , Iran 20,21 , Iraq 22 and China. 23 On the other hand, studies conducted in Qalyobia 14 and Alexandria 17 (Egypt) found no significant differences between prevalence of ADHD among males and females.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding gender, this study found significantly higher prevalence of ADHD among boys (14.5) than girls (3.6). This is consistent with results reported by studies conducted in Egypt 11,15,16,18 , Iran 20,21 , Iraq 22 and China. 23 On the other hand, studies conducted in Qalyobia 14 and Alexandria 17 (Egypt) found no significant differences between prevalence of ADHD among males and females.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence rate of ADHD among the studied students in this study was 9.6%. The reported rate in this study is higher than that reported by studies conducted in Menofia governorate, Egypt (2014) 11 (6.9% among 1,362 primary school students), El-Minia city, Egypt (2010) 15 and other studies in Egypt may be due to differences in age of the children under study and differences in the sample size and tool and methodology of the study in addition to differences in the sociodemographic and cultural characteristics of the study population. Alhraiwil, et al 2015 19 in their review about ADHD in Arab countries found that studies which used Conner rating scale for parents and teachers showed prevalence range of ADHD between 3.4% and 9.9%, on the other hand studies which used clinical interviews (in Egypt) or self-reported questionnaire (in Iraq) showed prevalence range between 14.75% to 19.6%.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The characteristics of these studies are summarized in Table 1. Selected studies were conducted in Nigeria [30][31][32], Sudan [33], Uganda [34], Congo [35], Kenya [36,37], Egypt [38][39][40][41], and Ethiopia [42]. Age at diagnosis of ADHD varies from 4 to 18 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…However, another study in Menoufia Governate, Egypt among ADHD primary school children by Farahat et al, (2014) reported a ratio of 1:3.5, this ratio difference could be attributed to the hospital-based sample in the current study versus a community based last mentioned study.12…”
Section: Discussionmentioning
confidence: 57%